Implementation of Maintenance Value Stream Mapping and Overall Equipment Effectivenes Methods to Increase the Effectiveness of Production Equipment in Andesite Mining Companies - Irawanti, Eka; Prabowo, Herry Agung; Hasbullah, Habullah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
The Andesite mining company experienced a 12.46% deviation between demand and actual delivery, primarily caused by reduced machinery effectiveness, which led to unmet production targets. This study aims to maximize production capacity and improve delivery performance through the application of the Overall Equipment Effectiveness (OEE) method. Furthermore, the Maintenance Value Stream Mapping (MVSM) approach was employed to evaluate and enhance the maintenance system by visualizing maintenance process flows and ensuring optimal facility functionality.The results showed that the initial OEE value of 39.72% increased significantly to 85.74% after the implementation of improvement strategies. This improvement was closely associated with the application of MVSM, which also enhanced the Value Added (VA) performance of several maintenance activities. For Conveyor gearbox maintenance, the VA value increased from 10.32% to 57.91%, while Motor Feeder maintenance improved from 18.04% to 61.04%. Screen sieve replacement for 1–2 increased from 17.04% to 32.50%, and Screen sieve replacement for 3–5 improved from 17.62% to 33.07%. Screen sieve replacement for 2–3 also showed an increase from 17.02% to 32.56%. Meanwhile, the VA values for small conveyor roller bearings maintenance remained constant at 62.39%, jaw setting maintenance at 20.78%, and large conveyor roller bearings maintenance at 41.78%. These findings indicate that the integration of OEE and MVSM methods effectively enhances maintenance performance and overall production efficiency, contributing to improved delivery reliability.